2015
DOI: 10.1682/jrrd.2014.09.0208
|View full text |Cite
|
Sign up to set email alerts
|

No association between body composition and cognition in ambulatory persons with multiple sclerosis: A brief report

Abstract: There is evidence that body fat is inversely associated with cognitive functioning in adults from the general population, and this has been associated with systemic inflammation. The association between body fat and cognition might further be augmented in the presence of an immune-mediated, inflammatory disease such as multiple sclerosis (MS). This cross-sectional study investigated the associations between objective measures of body composition and cognitive function in 60 persons with MS. Participants underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Indeed, disability status was significantly correlated with symptoms in the present study and may be an important physiological factor for consideration as a moderating variable in the correlation between body composition and outcomes in MS (Pilutti & Motl, 2019). For example, others studies have reported associations among bone health indicators and cognition (Batista et al, 2012; Sandroff, Hubbard, Pilutti, & Motl, 2015); however, controlling for disability status attenuated those associations in MS. Other factors to consider may be various physiological and psychological factors, including muscular strength, aerobic fitness, and health-related quality of life, because one study of persons with MS demonstrated significant correlations between those factors and %BF, LM, and BMC (Pilutti & Motl, 2019). Clinical researchers may consider future focal research including persons with varying disability aimed at understanding factors associated with debilitating symptoms in MS that can be modified using rehabilitative therapies.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, disability status was significantly correlated with symptoms in the present study and may be an important physiological factor for consideration as a moderating variable in the correlation between body composition and outcomes in MS (Pilutti & Motl, 2019). For example, others studies have reported associations among bone health indicators and cognition (Batista et al, 2012; Sandroff, Hubbard, Pilutti, & Motl, 2015); however, controlling for disability status attenuated those associations in MS. Other factors to consider may be various physiological and psychological factors, including muscular strength, aerobic fitness, and health-related quality of life, because one study of persons with MS demonstrated significant correlations between those factors and %BF, LM, and BMC (Pilutti & Motl, 2019). Clinical researchers may consider future focal research including persons with varying disability aimed at understanding factors associated with debilitating symptoms in MS that can be modified using rehabilitative therapies.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly to our secondary analysis results, a recent large study (n = 8713) of patients with MS revealed no association between the Processing Speed Test (PST) and BMI as continuous or categorical variable. 36 Contrastingly, other cross-sectional evidence has found that obesity is linked to reduced cognitive functions, particularly in executive, attention, and memory domains, which are highly prevalent in MS. 17 In addition, although an effect between BMI and cognitive function has been seen mostly in the aging healthy population and partially in a few MS studies, 17 , 18 the interaction between BMI and cognitive function in patients with MS, and the role of BMI as a risk factor for cognitive dysfunction are complex and highly debated. However, if an association exists between cognition and BMI, the mechanisms are unclear, and it might be through complex mechanisms that involved depression, exercise, or other factors associated with both obesity and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Obesity has been linked with cognitive dysfunction and brain volume loss in healthy adults, 7,8 and brain volume loss has been recognized as one of the best predictors for cognitive impairment in MS. 9,10 Although multiple studies have shown a link between cognitive impairment and brain volume loss in MS, it is unclear if this association is triggered by modifiable risk factors such as body mass index (BMI) and/or non-modifiable factors, such as genetics, or a combination of both. Cross-sectional studies, [11][12][13][14][15][16][17][18] provided preliminary and partial support for the relationship between high BMI and brain volume loss and cognitive dysfunction in MS, but there are also conflicting results. For example, Bove and colleagues (2019) and Galioto and colleagues (2019) did not show an association between BMI and cognition but Owji and colleagues (2019) demonstrated a negative correlation between BMI and cognitive function as measured by the Paced Auditory Serial Addition Test (PA-SAT) and Symbol Digit Modalities Test (SDMT).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the evidence from three Class iii studies and four Class iv studies support better physical fitness as being associated with better cognitive performance in persons with MS, whereas only one Class iv study did not report positive effects (Sandroff, hubbard, et al, 2015; see Figure 14.1). Of note, in this area, there are no rCTs (i.e., Class i or ii evidence) examining the effects of physical fitness on cognition.…”
Section: Discussionmentioning
confidence: 90%
“…Eight studies focused on physical fitness and cognition in MS. Of the eight published studies in this area, there are three Class iii studies (Prakash et al, 2010;Sandroff & Motl, 2012; and five Class iv studies (Batista et al, 2012;Beier, Bombardier, hartoonian, Motl, & Kraft, 2014;Prakash et al, 2007;Sandroff, hubbard, Pilutti, & Motl, 2015;. The primary difference between the Class iii and Class iv studies is that the Class iii studies involved healthy control comparison groups, whereas the Class iv studies did not.…”
Section: Comprehensive Review Of Evidencementioning
confidence: 99%